The Interactive Effects of Victim Race and Gender On Death Sentence Disparity Findings - Holcomb, Jeff (Homicide studies, 2004)
Several death penalty studies have examined whether victim race is associated with differential death sentencing outcomes; however, these studies tend to ignore the potential interaction of victim race and victim gender on decision-making outcomes. The present article examined the impact of the interaction of victim race and gender on death sentences in Ohio. When victim race and gender were considered, those homicides with white female victims were significantly more likely to result in a death sentence than homicides with other victim characteristics. This finding expands on previous research by identifying a specific victim gender-race combination, white female victim, as an extra- legal factor that may partially explain previously identified race of victim disparities in death sentencing